Lessons Learned from the Yellowhead Tribal Services Agency Open Custom Adoption Program - Carrière, Jeannine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
Following a historic meeting of staff with Alberta Children’s Services and the Yellowhead Tribal Services Agency (YTSA), a pilot program, the YTSA Open Custom Adoption, was developed. The agency initially researched existing adoption models in the Northwest Territories, British Columbia and in the Cheyenne Nation in the United States. An advisory committee, comprised of one Elder from each member First Nation community, was asked to provide guidance and direction throughout the project. From 2000 to 2010, YTSA placed over a hundred children in adoptive homes without any adoption breakdowns (Peacock & Morin, 2010). Although the agency has now closed its doors, there are lessons to be learned from the YTSA Open Custom Adoption program which is still viewed as an advanced model of adoption service inspired by traditional First Nation teachings and child caring. This article is a review of lessons learned from this agency and in particular, the importance of connectedness to family, community culture and nationhood for Indigenous children and adoption.